A Study on the Impact of Government Complexity and Regional Governmentas Size on Human Development Index in North Sumatera, Indonesia (Global Journal of Management and Business Research, 2014)
This study aims to determine the impact of the government complexity and regional government's size on the human development index in North Sumatera province. This is an explanatory research survey. The variables used in the study are, namely; the government complexity, size of regional government and human development index. Meanwhile, the population involves all the 33 districts/cities in the North Sumatera with a sample taken from a period of 2005-2012 derived using the purposive sampling approach. In addition, The respondents of this study is on the government apparatus who represent the human development programs' planners in several offices involved in the Tanjungbalai city and Asahan, South Labuhan Batu, North Labuhan Batu and Batubara districts with the number of 88 people selected as the sample using the purposive random sampling method. The returned questionnaires were 62 questionnaires. This study is a mixture of quantitative and qualitative studies. The result of the study has revealed that simultaneously and partially that the government complexity and the regional government's size variables simultaneously affect the human development index in North Sumatera.
Keywords: human development index; government complexity; purchasing power parity; population density and regional government#x2019; s size